ETHICS IN THE GLOBAL SOUTH - Schwartz, Michael; Harris, Howard; Comer, Debra R. (Research in ethical issues in organizations, 2017)
This volume includes works by authors from the global South and contributions about ethical issues in the global South, including the responses to famine in East Africa, India and Indonesia, and the applicability of international guidelines and ethical frameworks in South Africa.